The Relationship Between Resilience and Work Motivation on Nurses Performance - Dwi Rohyani; Zuhairotun Nayyiroh (Indonesian Journal of Global Health Research, 2026)
Nurse performance is a major factor that determines the quality of patient care. Performance is defined as the ability to carry out tasks optimally in accordance with applicaeble professional standards. Nurse performance can be influenced by various factors, including psychological factors such as resilience and work motivation. This study aimed to determine the relationship between resilience and work motivation with nurse performance at RSUD X, Bogor Regency. This study employed a quantitative research design with a correlational approach and a cross-sectional design. The population consisted of all nurses at RSUD X, Bogor Regency, with a sample of 94 nurses selected using purposive sampling. The research instruments used were questionnaires, including the resilience questionnaire (CD-RISC 10), work motivation questionnaire, and nurse performance questionnaire. The resilience instrument showed good validity (0,711-0,906) and high realiability (Cronbach’s alpha = 0,940), while the work motivation and nurse performance questionnaires demonstrated acceptable validity range (0,303-0,639 and 0,317-0,706, respectively). Data analysis was conducted using the Fisher’s Exact test. The results showed a significant relationship between resilience and nurse performance (p = 0,003), as well a significant relationship between work motivation and nurse performance (p = 0,001). This study concludes that both resilience and work motivation are significantly associated with nurse performance.